Application of digital marketing in the efforts to develop MSMEsin Baleangung Village, Grabag District, Magelang Regency - Pristi Sukmasetya; Muliasari Muliasari; Amelia Anggraini; Famila Zidda; Hasna Nur Arifaini; Avian Ali Mas'ud (BEMAS: Jurnal Bermasyarakat, 2023)
Baleagung Village is one of the villages in Grabag District, Magelang Regency which has several MSMEs such as Cilok Baraya, Griya Sangkrip bird cages and FEED Concentrate. However, MSME actors still depend only on direct marketing (face to face), even thoughthe era is increasingly digital. This is due to the lack of knowledge and doubts by MSME actors about existing technology to help their marketing. Seeing this, the purpose of this community service activity is to provide MSME actors with the knowledge and courage to be able to apply digital marketing in their marketing so that they can help expand their reach. The method used is digital marketing outreach and training, creating digital marketing platforms, mentoring activities, to monitoring and evaluation. The results ofthis activity are increased knowledge, a desire to progress, and the ability of MSME actors to carry out marketing so that in the end the resulting products can be recognized by a wider audience and have a greater opportunity to develop existing markets